Discipline, conflict, violence and honor: the internal jurisdiction at the cathedral chapter in Santiago de Compostela (1465-1602) - Iglesias Ortega, Arturo (Cuadernos de Historia Moderna, 2021)
The Cathedral Chapter of Santiago de Compostela had got jurisdictional competencies that conflicted with the limitations that its archbishop tried to impose since the end of the Middle Ages. Starting from the Chapter acts and the notarial protocols, we analyze the evolution of violence and indiscipline crimes committed by the cathedral staff and judged through the Chapter way of correction and punishment called Beate Jacobe to verify the effects of the Council of Trent.